The mouth or the nose: the past, present, and future of ultra-slim gastroscopy of the upper gastrointestinal tract in pediatrics - Tran, Paul; Lee, Rose; Mencin, Ali; Ryan, Matthew; Friedlander, Joel A.; Manfredi, Michael A. (Frontiers in Pediatrics, 2025)
BackgroundUltra-slim, flexible endoscopy pioneered for the evaluation of luminal diseases of the airway, has been used for over 40 years. In the late 20th century, it was adopted in the gastrointestinal specialties for evaluation of the digestive tract with and without the need for sedation. Since the advent of this technology, numerous descriptions of its use in small anatomic areas have been described. These include stricture evaluation and therapy, ostomy evaluation, biliary interventions, and diagnostic endoscopic evaluation of pediatric patients. This manuscript reviews the availability and clinical utility of ultra-slim flexible endoscopes, describes technical approaches, and highlights the potential value the technology offers to pediatric providers and healthcare systems.MethodsA comprehensive literature review was conducted on the use of ultra-slim endoscopes in the pediatric and adult gastroenterology. Expert discussions were held to evaluate current practices, indications, and equipment. The resulting expert opinion was generated to summarize pertinent information regarding key techniques, indications, and practical considerations for implementation in pediatric settings.ResultsAlthough ultra-slim endoscopes started their use in small-space adult gastroenterology procedures, they have shown significant benefit and value within pediatrics. The literature documents their use in both sedated and unsedated environments, including transnasal upper endoscopy, variceal surveillance, esophageal stricture evaluation, neonatal endoscopy, enteral tube placement, and ostomy assessment.ConclusionUltra-slim flexible endoscopy provides pediatric gastroenterologists with a valuable diagnostic and therapeutic tool. When used appropriately, either with or without sedation, it has the potential to increase clinical efficiency, reduce procedural risk, and improve access to care.